2018
DOI: 10.1080/08957959.2018.1558223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrostaticity on the structural stability of carbonates at lower mantle pressures: the case study of dolomite

Abstract: We have conducted high pressure far-infrared absorbance and Raman spectroscopic investigations on a natural iron-free dolomite sample up to 40 GPa. Comparison between the present observations and literature results unraveled the effect of hydrostatic conditions on the high pressure dolomite polymorph adopted close to 40 GPa, i.e. the triclinic Dol-IIIc modification. In particular, non-hydrostatic conditions impose structural disorder at these pressures, whereas hydrostatic conditions allow the detection of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…The lattice distortions could significantly affect the chemical bonding environments in MgCO 3 as well as its structural stability with increasing pressure. This result sheds new light on the stability of carbonates under quasi-hydrostatic conditions, indicating that the effect of hydrostaticity shall be taken into account for modeling the deep-carbon cycle (Efthimiopoulos et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The lattice distortions could significantly affect the chemical bonding environments in MgCO 3 as well as its structural stability with increasing pressure. This result sheds new light on the stability of carbonates under quasi-hydrostatic conditions, indicating that the effect of hydrostaticity shall be taken into account for modeling the deep-carbon cycle (Efthimiopoulos et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…GPa in this study ( Figure 1). It was previously reported that the v 1 mode of dolomite split into four separate Raman peaks using Ne as a PTM at ~39 GPa, whereas only one peak was observed within the same Raman region when argon was used as a PTM (Efthimiopoulos et al, 2018). Fiquet et al (2002) carried out synchrotron XRD experiments on magnesite MgCO 3 up to 83…”
Section: Lattice Distortion Of Mgco 3 At High Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…As abundant CO 2 -bearing minerals, the thermodynamic properties of carbonates are of particular importance. A significant number of Raman studies of the high-pressure behavior of carbonate minerals have been reported, including aragonite, calcite, vaterite, and other high-pressure CaCO 3 polymorphs (Fong and Nicol 1971;Nicol and Ellenson 1972;Salje and Viswanathan 1976;Liu and Mernagh 1990;Hess et al 1991;Kraft et al 1991;Biellmann and Gillet 1992;Gillet et al 1993;Suito et al 2001;Shi et al 2012;Pippinger et al 2015;Koch-Müller et al 2016;Liu et al 2017;Lobanov et al 2017;Maruyama et al 2017;Bayarjargal et al 2018;Farsang et al 2018;Yuan et al 2019), azurite (Xu et al 2015), cerussite Liu 1997c, 1997b;Minch et al 2010b;Zhang et al 2013;Gao et al 2016), dolomite (Kraft et al 1991;Biellmann and Gillet 1992;Gillet et al 1993; Efthimiopoulos et al 2017Efthimiopoulos et al , 2018Farsang et al 2018;, ikaite…”
Section: Introductionmentioning
confidence: 99%
“…In [ 65 ], studies of the infrared spectra of natural iron-free dolomite were carried out. A combined study of infrared absorption and Raman scattering on a natural dolomite sample CaMg 0.98 Fe 0.02 (CO 3 ) 2 was performed [ 66 ].…”
Section: Introductionmentioning
confidence: 99%